Determination of safe route to school for walking children / Intan Syuhana Aziz - Aziz, Intan Syuhana (2015)
Injuries or fatalities change lives, especially for children as they are vulnerable emotionally and physically. Every child who leaves for school is expected to return home in safe and sound condition. Hence, children’s safety at school has been associated with various views, including road safety aspects. Travel route safety has become a major concern among parents, children, and school personnel. Heavy volume of traffic with poor road maintenance has been acknowledged as the contributing prospect that often makes road safety a remarked issue. This topic is more upsetting when the road safety aspects around the school vicinity are overlooked. As a result, parents and children reckon that it is not safe to walk, hence decreasing the number of school children who do so. In addition to that, evoking the number of parents and children who prefer motorized vehicle as a common mobility mode worsens the existing congested traffic condition. Although the Malaysian Department of Town and Regional Planning (DTCP) has laid out a guideline concerning school siting parameter, the road safety aspect pertaining to travel route distance taken was not thoroughly highlighted. Corresponding to the matter, this study evaluated the school siting parameter effects towards school children’s road safety. This study had been limited to six primary and secondary schools in Johor Bahru, Malaysia. Theoretical and empirical techniques were emphasized in the research methodology. Questionnaire survey was distributed to 553 students in six selected schools and interview session with related authorities was done as part of preliminary work. Besides, Statistical Package of Social Science (SPSS) and Geographic Information System (GIS) were utilized in investigating mobility mode pattern, school coverage area, and route taken to school. The results from all schools showed similar pattern, whereby motorized vehicle (parents vehicle and school bus) had been discovered as the ideal mobility mode to school. On top of that, statistical analysis tabulated that distance and age were never a factor in mobility mode choice. Furthermore, network analysis was done in establishing the shortest route taken to school, where it showed that children used the main road as part of their travel route. In addition, alternative route to school was established, by avoiding or minimizing the use of main road, yet it indicated that children needed to take a longer distance to get a safer travel route. Hence, a new safe route to school map was established with additional discussion of proposed safety aspects, such as parking bay for school bus and parents’ vehicle, zebra crossing, road patrol, and pedestrian walk. This study proved that additional road safety aspects should be included in the school siting parameter guideline to ensure that school children’s road safety is thoroughly covered.